The HBV Specially-Related Long Noncoding RNA HBV-SRL Involved in the Pathogenesis of Hepatocellular Carcinoma. (8th July 2022) - Zhang, Cunzhen; Lu, Lei; Xin, Haibei; Zhang, Minfeng; Ding, Zhiwen; Li, Qiaomei; Chen, Kuang; Hu, Minggen; Liu, Shupeng; Li, Nan
Abstract : Hepatitis B virus (HBV) is one of the major risk factors for HCC (hepatocellular carcinoma) occurrence with a diverse role in the pathogenesis of HCC. More works need to be performed to elucidate a more thorough understanding of the molecular mechanisms involving in HBV-induced HCC, although some mechanisms such as genome integration have been reported. In the present study, aberrantly expressed lncRNAs were identified between HCC tumor tissues with or without HBV infection. Among these molecules, HBV specially-related long noncoding RNA (HBV-SRL) was further found to correlate with poor prognosis and a shorter overall survival time in HCC patients with HBV infection. Additionally, HBV-SRL was found function as oncogene by upregulating the NF- κ B2 expression. These data suggest that HBV infection altered gene expression pattern in liver cells which contributed to HBV-related HCC development, and HBV-SRL may serve as a new molecular marker or potential therapeutic target of HBV-related HCC.